Family medical care Volume 3: major systrms of the body, and emergencies - Knight, John F (Signs Publishing Company, Warburton, Vic., 1990)
Contents: Major systems of the body and emergencies : Section 1: The heart and blood vessel system (the cardiovascular system) - Section 2: The breathing apparatus (the respiratory system) - Section 3: The food system (the gastrointestinal system) - Section 4: Emergency first aid
Keywords: Parenting